Ações culturais para mitigação de danos em contextos de desastres e conflitos civis e armados - Mattos, Thiago de (Universidade Federal de São Carlos, 2025)
This work focused on cultural actions aimed at mitigating damage in contexts of disasters and civil and armed conflicts. Thus, the key research question was: “What cultural actions are developed in contexts of disasters and civil and armed conflicts?” The main objective was to propose recommendations for cultural actions that could be implemented in these scenarios to mitigate damage, with an emphasis on preserving cultural identity and ensuring free access to information. To achieve this objective, the following specific goals were established: reviewing the scientific literature on cultural actions; defining disasters, civil and armed conflicts, and their relationship with social, economic, identity-related, and cultural issues; and identifying strategies for cultural actions adopted in these contexts. The research adopted a qualitative, applied approach, with exploratory objectives and bibliographic and documentary procedures. Institutional documents, scientific articles, cultural productions, and news related to the topic were examined through categorical content analysis, aiming to identify, categorize, and interpret patterns and meanings present in the collected material. The results contributed to the formulation of cultural strategies aimed at strengthening the resilience of affected communities and ensuring cultural rights even in situations of disasters and civil and armed conflicts.
Cultural actions to mitigate damage in contexts of disasters and civil and armed conflicts
Keywords: Ação cultural; Conflitos armados; Desastres; Conflitos civis; Cultural actions; Armed conflicts; Disasters; Civil conflicts; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; 16. Paz, Justiça e Instituições Eficazes; 4. Educação de Qualidade; 10. Redução das Desigualdades